A retrospective evaluation of the impact of a dedicated Obstetric and Neonatal transport service on transport times within an Urban setting - de Vries, Shaheem (Division of Emergency Medicine, 2023)
Objective: To determine whether the establishment of a dedicated obstetric and neonatal flying squad resulted in improved performance within the setting of a major metropolitan area. Design and Setting: The Cape Town metropolitan service of the Emergency Medical Services was selected for a retrospective review of the transit times for the newly implemented Flying Squad programme. Data were imported from the Computer Aided Dispatch programme. Dispatch, Response, Mean Transit and Total Pre-hospital times, relating to the obstetric and neonatal incidents was analysed for 2005 and 2008. Results: There was a significant improvement between 2005 and 2008 in all incidents evaluated. Flying Squad dispatch performance improved from 11.7% to 46.6% of all incidents dispatched within 4 minutes (p< 0.0001). Response time performance at the 15- minute threshold did not demonstrate a statistically significant improvement (p=0.4 .. ) although the improvement in the 30-minute performance category was statistically significant in both maternity and neonatal incidents. Maternity incidents displayed the greatest improvement with the 30-minute performance increasing from 30.3 % to 72,9%. The analysis of the mean transit times demonstrated that neonatal transfers displayed the longest status time in all but one of the categories. Even so, the introduction of the Flying Squad programme resulted in a reduction in a total pre-hospital time from 298 minutes to 184 minutes. Conclusion: The introduction of the Flying Squad programme has resulted in significant improvement in the transit times of both neonatal and obstetric incidents. In spite of the severe resource constraints facing developing nations, the model employed offers significant gains.